Novel Voltage Multiplier Topologies And Control Schemes For ZCS-SR Inverter Fed Voltage Multiplier Based X-Ray Power Supplies - -, Shahid Iqbal (2008)
This research work proposes novel single/three-phase VM topologies and control schemes for VM based X-ray power supplies to meet all above challenges.